Nutrient Content and Acceptability of Biscuits Subtitutes from Flour of Mackerel Fish (Rastrelliger Kanagurta L) (Medico Legal Update, 2021)
Mackerel (Rastrelliger kanagurta L) is widely available and contains nutrients. This fish has potential forprevention malnutrition problems in Indonesia, especially in South Sulawesi Province, but their utilization isnot optimal. The aims of this study was to determine nutrient content and acceptability biscuits subtitutes fromflour of mackerel fish. The design of this study was experimental by making biscuits through substitution withmackerel fish flour and divided into four concentration formulas, F0 = 0%, F1 = 5%, F2 = 10%, F3 = 15%.Each biscuit was subjected to a acceptability test using the organoleptic test method using hedonic scale.Analysis of protein content using the Kjehdal method, fat content using the shoxlet method, carbohydratescontent using the Luff Chroll method and minerals content using with AAS. The results of this study thatsubstitution of mackerel flour reduced the acceptance of biscuits, although the decrease was not significantin terms of color (p = 0.061) and texture (p = 0.356). A significant decrease in the acceptability score wasseen in the aroma aspect (p = 0.000) and the taste aspect (p = 0.000). F1 biscuits are the best formula, havinga carbohydrate content of 62.49%, 18.35% fat, 10.72% protein, 10.83 mg/L zinc and 230.95 mg/L iron. Thesubstitution of mackerel flour does not affect for acceptability of the color and texture aspects, but affectsfor aroma and taste, especially if the concentration of the addition is too high. Protein, iron, and zinc levelsincreased in the biscuits formula that was substituted for mackerel fish meal.